ATTACKLLYS OF ORGANIC SYSTEMS IN ELDERLY PATIENT OF A HEALTH'S PLAN OF THE STATE OF PARAÍBA - BRAZIL (Fiep Bulletin - online, 2012)
In the aging classification commeend by the World Health Organization (WHO), the brazilian legislation considers elderly person that with larger age or same to 60 years. However, in the aging process they are involved, besides the biological and physiologic aspects, another varied such as the hereditariness, the psychological state and the conditions socio - economic and cultural. It is starting from the relationship of those you varied that the aging singular process is constituted for each individual. To evaluate the prevalence of attacklly of the different organic systems involved in the process of human aging, in individuals between 60 and 100 years, of a health's plan that assists the state of Paraiba, Brazil, in the last five years. It is a documental study of prevalence, of sample for convenience, where a rising was accomplished, close to the database of a health's plan of the state of Paraíba, Brasil. With sample of 685 elderlys. The organic system of larger involvement was the osteomioarticular with 559 (51,5%) of the attacked older patients, followed by the system cardiocirculatory that presented 197 procedures accomplished finishing a percentile one of (18%) and finally the cutaneous and annexs system with 134 (12%). The aging process reaches in a progressive way all the systems of the organism, there is no doubt that the diseases that involve the system musculoesqueletic and the cardiovascular system grow exponentially with the age. In the studied group, the prevalence of referring procedures to the system osteomioarticular designate the presence of pathologies that they can determine the limitation for the acting of basic activities and you score of the daily life. Becoming important the professionals' of the health performance in those systems focusing the levels primary, secondary and tertiary of attention the health for a to age successful.
Keywords: Health; Aging; Health Plan.